Regional bit allocation and rate distortion optimization for multiview depth video coding with view synthesis distortion model - Zhang, Yun (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2013)
In this paper, we propose a view synthesis distortion model (VSDM) that establishes the relationship between depth distortion and view synthesis distortion for the regions with different characteristics: color texture area corresponding depth (CTAD) region and color smooth area corresponding depth (CSAD), respectively. With this VSDM, we propose regional bit allocation (RBA) and rate distortion optimization (RDO) algorithms for multiview depth video coding (MDVC) by allocating more bits on CTAD for rendering quality and fewer bits on CSAD for compression efficiency. Experimental results show that the proposed VSDM based RBA and RDO can improve the coding efficiency significantly for the test sequences. In addition, for the proposed overall MDVC algorithm that integrates VSDM based RBA and RDO, it achieves 9.99% and 14.51% bit rate reduction on average for the high and low bit rate, respectively. It can improve virtual view image quality 0.22 and 0.24 dB on average at the high and low bit rate, respectively, when compared with the original joint multiview video coding model. The RD performance comparisons using five different metrics also validate the effectiveness of the proposed overall algorithm. In addition, the proposed algorithms can be applied to both INTRA and INTER frames